2019
DOI: 10.1016/j.toxrep.2019.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of tamoxifen and simvastatin as the combination therapy for the treatment of hormonal dependent breast cancer cells

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 62 publications
1
14
0
3
Order By: Relevance
“…These findings clearly suggest that the cell membrane integrity was severely compromised by PtNPs and RA. For example, when T47D cells were exposed to tamoxifen and simvastatin combination, the leakage of LDH was significantly higher than that observed with the control treatment [62]. We have previously reported that treatment with the combination of silver nanoparticles and histone deacetylase inhibitors significantly increases the leakage of LDH, compared with that on individual treatment of human alveolar basal epithelial cells [63].…”
Section: Combination Of Ptnps and Ra Induces Lactate Dehydrogenase (Lmentioning
confidence: 85%
“…These findings clearly suggest that the cell membrane integrity was severely compromised by PtNPs and RA. For example, when T47D cells were exposed to tamoxifen and simvastatin combination, the leakage of LDH was significantly higher than that observed with the control treatment [62]. We have previously reported that treatment with the combination of silver nanoparticles and histone deacetylase inhibitors significantly increases the leakage of LDH, compared with that on individual treatment of human alveolar basal epithelial cells [63].…”
Section: Combination Of Ptnps and Ra Induces Lactate Dehydrogenase (Lmentioning
confidence: 85%
“…The importance of this interaction is intensified as atorvastatin may be prescribed with tamoxifen for cancer patients because of hypercholesterolemia. Apart from their lipid-lowering effects, statins have induced anticancer activity in different cancer cell lines (Ibrahim et al, 2019;Tutuska et al, 2020). Therefore, it is necessary to reduce the dose of tamoxifen in these patients due to synergistic drug interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are somewhat similar to other cancer types studies of statins therapy. For example, Ibrahim and colleagues (Ibrahim et al, 2019) reported that the simvastatin in combination of tamoxifen increased the apoptotic and necrotic cell death in breast cancer cells. Recently, Stine et al (2016) have shown that simvastatin may have therapeutic benefit for ovarian cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simvastatin + tamoxifenIn vitro and in vivo 1-An increase in the apoptotic and necrotic cell death 2-A decrease in VEGF and MMP-2/-9[252] Fluvastatin + vorinostatIn vitro and in vivo1-A robust apoptosis induction and inhibiting cancer growth 2-Enhancing vorinostat-induced histone acetylation 3-Inducing ER stress 4-Inhibiting the mTOR pathway and AMPK activation Synergistically suppression of the cell proliferation through sub-G1 and S-phase cell cycle arrest 2…”
mentioning
confidence: 99%